The role of Zai pits and integrated soil fertility management options in improving crop productivity for smallholder farmers in the drylands of Sub-Saharan Africa - Getare, Ednah Kerubo; Mucheru-Mucheru-Muna, Monicah; Muriu-Ng’anga, Felista (Journal of Aridland Agriculture, 2024)
The drylands of Africa are experiencing food insecurity due to prolonged drought and water scarcity which has a negative effect on crop production. In the drylands of Sub-Saharan Africa, many small holder farmers are experiencing low crop yields and economic returns as a result of poor soil fertility and water scarcity. This is because of the inappropriate soil and water conservation strategies used in the region. Zai pits have been used as a soil and water conservation strategy in the drylands of Africa in combination with integrated soil fertility management (ISFM) options to improve soil fertility, increase the overall crop yields and the economic returns. This review deals on the role of zai pits and integrated soil fertility management options in improving productivity for the small holder farmers in the drylands of Sub-Saharan Africa. Zai pits have been used to harvest water which ultimately improves soil moisture for crop production with the different fertility inputs applied in the pits for nutrient efficiency. To evaluate productivity and profitability in zai tillage system, yield, benefit cost ratio (BCR) and net benefits are used. In this study, different studies by researchers on the use of zai pits and integrated soil fertility management options have been discussed and this would be beneficial for other researchers who have interest in this field. Most studies have indicated that the zai pit technology is an important soil and water conservation strategy which in combination with the integrated soil fertility management (ISFM) options improves crop productivity in terms of yield and economic returns.